2005
DOI: 10.1063/1.1991989
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional imaging of individual hafnium atoms inside a semiconductor device

Abstract: The aberration-corrected scanning transmission electron microscope allows probes to be formed with less than 1-Å diameter, providing sufficient sensitivity to observe individual Hf atoms within the SiO 2 passivating layer of a HfO 2 / SiO 2 / Si alternative gate dielectric stack. Furthermore, the depth resolution is sufficient to localize the atom positions to half-nanometer precision in the third dimension. From a through-focal series of images, we demonstrate a three-dimensional reconstruction of the Hf atom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
156
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 240 publications
(159 citation statements)
references
References 22 publications
3
156
0
Order By: Relevance
“…Optical sectioning has been demonstrated in previous work for single Hf atoms in SiO 2 (van Benthem et al 2005) and for small Pt and Au nanoparticles in a TiO 2 powder (Borisevich et al 2006). The positions of single atoms were located in three dimensions by van Benthem et al (2005) with an error of less than a nanometre, while Borisevich et al (2006) showed that the reconstructed shapes of large particles are elongated along the optic axis. In this paper, we present results from experimental STEM optical sectioning of samples containing Pt and Au nanoparticles of varying size.…”
Section: Introductionmentioning
confidence: 99%
“…Optical sectioning has been demonstrated in previous work for single Hf atoms in SiO 2 (van Benthem et al 2005) and for small Pt and Au nanoparticles in a TiO 2 powder (Borisevich et al 2006). The positions of single atoms were located in three dimensions by van Benthem et al (2005) with an error of less than a nanometre, while Borisevich et al (2006) showed that the reconstructed shapes of large particles are elongated along the optic axis. In this paper, we present results from experimental STEM optical sectioning of samples containing Pt and Au nanoparticles of varying size.…”
Section: Introductionmentioning
confidence: 99%
“…For the first time, Pennycook et al have demonstrated the imaging of individual Hf atom in the silicon oxide interface between a Hf oxide high-k and the silicon substrate [37]. This is shown in Figure 8.…”
Section: Materials Characterizationmentioning
confidence: 99%
“…been demonstrated previously [21,22]. In a non-confocal geometry, however, this approach can only be used for high-resolution imaging as the 3D transfer function for incoherent STEM imaging shows a missing cone which results in significant elongation in 3D images of laterally extended objects [23].…”
Section: Using This Reduced Depth Of Focus To Retrieve 3d Informationmentioning
confidence: 99%